Banking model of corporate waqf: an analysis of Wakaf Selangor Muamalat / Asharaf Mohd Ramli and Abdullaah Jalil - Ramli, Asharaf Mohd; Jalil, Abdullaah (2013)
Purpose - This study aims to analyse the structure of the corporate waqf model applied in “Wakaf Selangor Muamalat” which has been jointly established by Perbadanan Wakaf Selangor (PWS) and Bank Muamalat Malaysia Berhad (BMMB).